Analisis Peramalan Volume Penjualan CV Tirta Anugerah Abadi Menggunakan Metode Exponential Smoothing with Trend pada POM-QM - Nurul Hidayat; Muhammad Rully Febrian; Silvana Yusuf (Master Manajemen, 2025)
The increasing competition in the bottled drinking water distribution business in Tarakan City compels companies to improve sales forecasting accuracy as a basis for strategic decision-making. This study aims to analyze the effectiveness of the Exponential Smoothing with Trend method implemented through the POM-QM software in predicting the sales volume of CV Tirta Anugerah Abadi. Monthly sales data over the past two years were quantitatively analyzed using the Exponential Smoothing model with various smoothing parameter combinations. The results indicate that the parameter combination of α = 0.7 and β = 0.1 yields the lowest forecasting error, with a MAPE value of 1.24%. These findings demonstrate that the applied method is highly accurate and reliable for sales forecasting, thus supporting the company in more efficient stock, production, and distribution planning. The implications of this research not only enrich the literature on the application of modern forecasting methods in the local distribution sector but also provide practical contributions to company management in data-driven decision-making.